Pengaruh Return on Equity, Quick Ratio, dan Debt to Equity Ratio terhadap Nilai Perusahaan Sektor Teknologi di BEI periode 2022–2024 - Muhammad Rafi Triyanto; Saqofa Nabilah Aini (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This research examines the analysis of Return on Equity (ROE), Quick Ratio (QR), and Debt to Equity Ratio (DER) on corporate valuation, as assessed by Price-to-Book Value (PBV), within technology firms listed on the Indonesia Stock Exchange (IDX) during the period from 2022 to 2024. The primary aim of this investigation is to ascertain the effects of profitability, liquidity, and leverage both in isolation and in conjunction on market valuation in an industry characterized by innovation and intangible assets. This research employs panel data regression analysis utilizing EViews 13 as the quantitative methodology. The findings reveal that ROE significantly enhances PBV, indicating that investors place considerable importance on firms that are capable of generating substantial returns on equity for shareholders. Conversely, QR and DER appear to have no discernible impact on PBV. This observation can be attributed to the unique nature of technology companies, wherein investors prioritize factors other than short-term liquidity and leverage. Nonetheless, when assessed collectively, the three metrics illuminate the variations in corporate value. These results suggest that while financial stability indices exert a positive yet comparatively subdued effect on investor sentiment within the technology sector, profitability remains a paramount determinant. The study elucidates the financial determinants that influence corporate value in innovation-driven industries, providing valuable insights for managers and investors alike.